Environmental hotspot analysis of primary copper production in China and its future improvement potentials. (10th October 2022) - Lu, Tao; Tikana, Ladji; Herrmann, Constantin; Ma, Yibing; Jia, Jinping
Abstract: The production of resources e.g., copper (Cu) has induced many environmental issues worldwide, due to the growing demand to satisfy the world growing population. China, as the largest Cu production country in the world, deserves a special attention. However, the Life Cycle Assessment (LCA)-based environmental profile of Cu produced in China remains unclear due to insufficient representativeness, inconsistency of methodologies applied, and absence of reliable upstream datasets. In the present study, this critical gap was filled using globally harmonized LCA methodologies and facility-level data, technologically representing 77% of China's total Cu production capacity, with consideration of environmental burden embedded in upstream raw materials. Environmental issues were prioritized using LCA weighting and normalization method, while key contributing factors were identified via Life Cycle Impact Assessment (LCIA). Weighted and normalized results showed that Global Warming Potential (GWP) was found to be the priority issue whose contribution to the overall environmental impact reached up to 47%. LCIA results demonstrated that the environmental impacts of China Cu production were primarily caused by production process of raw materials (51%–66%), followed by fuels used for transport by sea and land (11%–22%) and electricity consumption (5%–12%), depending on impact categories. Based on the study results and the importance of GWP, special attention was given to energy systems and direct GWP relevant emissions, by investigating smelting technologies. Five ways towards a more environmentally improved Cu industry associated with the challenges to be addressed were put forward in the outlook (e.g., the use of green electricity can effectively reduce CO2 emission by 14%–29%).